A new prenylated xanthone from the stem bark of Calophyllum lowii - Jamaluddin, Nur Amirah; Ee, Gwendoline Cheng Lian; Teh, S. S.; Mah, S. H.; Md. Sukari, Mohd. Aspollah (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia, 2013)
Our detailed study on the chemical constituents of the stem bark of Calophyllum lowii has resulted in the isolation and characterization of one new xanthone calowiium (1) along with three other xanthone derivatives – caloxanthone L (2), β-mangostin (3), and macluraxanthone (4). Several triterpenoids and steroids, viz. friedelin (5), stigmasterol (6) and sitosterol (7) were also successfully isolated from this plant. The structures of these components were established by means of spectroscopic analysis –nuclear magnetic resonance (NMR 1D, 2D), UV, FTIR, and mass spectrometry.